Pengaruh Partisipasi Eksekutif Dan Kompleksitas Sistem Terhadap Sistem Informasi Pada Perusahaan Konstruksi Di Kota Mataram - Baiq Adriani Ulfa (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2020)
The title of this research is “The Excecutives Participation and System Complexity Concerning The Development of Information System at the construction Company in Mataram City” which is intended for knowing the simultaneously and partially influence between excecutive’s participation and system complexity concerning the development of information system. The sample determined which is used in this research is the stratified random sampling method with 56 people samples. The hypothetic test which used is the double linier regression. The F test is used for knowingthe influence of independent variable concerning the dependent variable concerning the dependent variable partially. Based on the analysis which have done before, known that the excecutive’s participation and system complexity variable is influenced simultaneously concerning the development of information system. The result of second hypothetic analysis showed that the eexecutive’s participation had influenced partially concerning the development of information system, while system complexity had it. Based on the research result that have gotten, the next researcheris hoped to develop more sample or to add the other variable which is predicted that it has influence ininformation system development, like the communication of user developerand user affect and take a sample industry building on process (continues product).